Colombia : 2020 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Colombia. (IMF Staff Country Reports; Country Report ;, 2020)
This 2020 Article IV Consultation with Colombia highlights that with the disruptions associated with the coronavirus disease 2019 pandemic and with lower oil prices, real gross domestic product (GDP) is projected to contract by 2.4 percent in 2020. In the near term, disruptions associated, directly and indirectly, with the pandemic are expected to generate a recession of -2.4 percent in 2020. Weaker domestic demand from the shutdown efforts is expected to partially offset lower external demand and commodity prices, such that the current account deficit is projected to rise to 4.7 percent of GDP. In the wake of exceptional shocks and risks, recent monetary easing is welcomed by the IMF and accommodation should continue to support the economy if underlying inflation and inflation expectations remain moderate. Continued liquidity support should be provided as required, and available capital buffers in the banking system should be used as needed. All available space under the fiscal rule can be used to meet unforeseen health expenditures and for countercyclical spending to further support the economy through recession.